Analisis Retrospektif Hasil Pemeriksaan Tiroid (TSH dan FT4) dengan Metode ELFA di RSUD Dr. Doris Sylvanus Palangka Raya - Eleventi Oktarina Putri; Antoni Aldo Danendra Sawal; Muhammad Ihza Lisan Shidqi; Yanti Sunaidi (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2025)
Thyroid disorders are among the most prevalent endocrine conditions globally, demanding precise diagnostic methodologies for effective management. Epidemiological data on thyroid disorders in Kalimantan is still limited. This study aims to re-analyze retrospective data on .thyroid stimulating hormone (TSH) and free thyroxine (FT4) levels measured using the Enzyme Linked Fluorescent Assay (ELFA) method in 2017 at RSUD Dr. Doris Sylvanus Palangka Raya, evaluate them with the latest guidelines, and validate the ELFA method. Data from 87 patients with suspected thyroid dysfunction were subjected to descriptive statistics, Chi-square tests, Spearman's correlation, and Receiver Operating Characteristic (ROC) curve analysis. Patients were predominantly female (n=67, 77%). Hormone distribution showed a tendency towards hyperthyroidism, with 48.3% (n=42) of patients having low TSH and 27.6% (n=24) having high FT4. Statistical analysis showed no significant association between gender and TSH (χ² = 1.277, df = 2, p = 0.528) or FT4 (χ² = 3.240, df = 2, p = 0.198) levels. However, a very strong and significant physiological relationship was found between TSH and FT4 levels, both categorically (χ² = 24.576, df = 4, p < 0.001) and correlationally (r = -0.503, p < 0.001). ROC analysis proved that the ELFA method has very good diagnostic accuracy with an Area Under Curve (AUC) of 0.915 (95% CI: 0.835–0.995, p < 0.001). The profile of thyroid disorders in this region is dominated by a hyperthyroidism pattern, and historical data from the ELFA method has been proven to remain valid and clinically relevant for epidemiological studies. These findings affirm that data generated by ELFA technology in 2017 remains robust and clinically valid when interpreted through the lens of modern guidelines. The study underscores the value of simultaneous TSH-FT4 testing and supports the sustained utility of older, yet reliable, immunoassay technologies, particularly in resource-limited settings, contributing to longitudinal epidemiological understanding of thyroid disorders in the region.